Spatial advertisement in political campaigns - Anja Prummer (Queen Mary University of London, School of Economics and Finance, 2016)
This paper characterizes the optimal advertising strategy of candidates in an election campaign, where groups of heterogeneous voters are targeted through media outlets. We discuss its effects on the implemented policy and relate it to the well-documented increase in polarization. Additionally, we empirically establish that polarization displays electoral cycles. These cycles emerge in the model as candidates find it optimal to cater to different groups of voters and thus to adjust policies. Further, technologies that allow targeting voters more precisely tend to increase polarization. Our prediction is confirmed empirically as an increase in internet penetration leads to higher polarization.
Keywords: D85; D72; D83; 330; Targeting; Media; Networks; Voting